Predictors of health-related quality of life among patients with diabetes on follow-up at Nekemte specialised Hospital, Western Ethiopia: a cross-sectional study - Bikila Regassa Feyisa; Mekdes Tigistu Yilma; Belachew Etana Tolessa (BMJ Open)
Objective To assess health-related quality of life (HRQoL) and its predictors among patients with diabetes on follow-up at Nekemte Specialised Hospital in Western Ethiopia.Design, setting and participants This facility-based cross sectional study was conducted among 224 patients with diabetes mellitus (types I and II) on follow-up at one of the public hospitals in western Ethiopia. Respondents were selected by systematic random sampling and interviewed with the aid of a questionnaire.Main outcome measured HRQoL was measured by using the Medical outcomes study 36-item Short Form (SF-36) Health Survey from 15 April to 5 June 2019. A structured questionnaire was used for data collection from participants selected by systematic random sampling. Multiple linear regression was used for the final model.Result A total of 215 patients with diabetes consented and completed the study, giving a response rate of 96%. The mean score of the overall HRQoL of the study participants was 50.3±18.1. The highest mean score was obtained in the physical functioning domain and the lowest mean score in the general health domain. Age, education status, history of smoking, feeling of stigmatisation and body mass index were inversely associated with the overall HRQoL. Gender (male), marital status (currently married), absence of comorbidity and absence of chronic complications related to diabetes mellitus were positively associated with overall HRQoL.Conclusion The overall HRQoL of patients with diabetes on follow-up at the study area was found to be moderate. General health, mental health, bodily pain and vitality were the most affected domains. Both the mental and physical components need to be considered when caring for the patients with diabetes on follow-up beyond provision of treatment.